2017
DOI: 10.1007/s00256-017-2657-y
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic resonance imaging appearance of the anterolateral ligament of the knee in association with anterior cruciate rupture

Abstract: ALL injury was identified in only one-tenth of cases of ACL rupture. MRI changes can be reliably identified with strong agreement between observers. ALL injury is found more frequently on MRI within 6 weeks of the knee injury (compared to scans performed after this time period) suggesting that some injuries may resolve or become less visible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…The reason meniscal tears did not have a significant relationship with residual ALRI might have been because most of the meniscal tears were repaired instead of meniscectomy. Factors regarding anterolateral structure or iliotibial tract injury were not investigated in the present study because the sensitivity and specificity of detecting these damages with image evaluation remain controversial [22][23][24]. As for the ATT side-to-side difference, it showed weak negative association with absolute residual acceleration based on univariate analysis, however, multivariate analysis showed no correlation between them.…”
Section: Discussionmentioning
confidence: 86%
“…The reason meniscal tears did not have a significant relationship with residual ALRI might have been because most of the meniscal tears were repaired instead of meniscectomy. Factors regarding anterolateral structure or iliotibial tract injury were not investigated in the present study because the sensitivity and specificity of detecting these damages with image evaluation remain controversial [22][23][24]. As for the ATT side-to-side difference, it showed weak negative association with absolute residual acceleration based on univariate analysis, however, multivariate analysis showed no correlation between them.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, criteria for injuries of similar ligamentous structures are used to define ALL tears, such as peripheral edema, irregularity of fibers, discontinuity, and bone avulsions. 7 , 33 , 36 38 , 55 57 The bone avulsion occurs at its distal insertion and corresponds to Segond fractures according to some authors 1 , 35 , 58 , 59 (Fig. 7 ).…”
Section: Allmentioning
confidence: 92%
“… 37 Some studies failed to identify the association between ALL MRI abnormalities and lateral meniscus tears in patients with a ruptured ACL, which makes this association still a matter of controversy. 37 , 55 Although not statistically significant, Kosy et al 55 showed a tendency of higher incidence of lateral meniscus tears in association with ALL abnormalities, which may be caused by the rotational stress in ACL injuries.…”
Section: Allmentioning
confidence: 94%
See 1 more Smart Citation
“…62 Another study showed good interobserver reliability in identifying injuries, but that only 10% of patients with a torn ACL have an injured ALL. 59,64 Some of the recent attention paid to the ALL in the literature is related to some authors' claims that it might cause the avulsion portion of a Segond fracture. The Segond fracture has historically been thought to be due to avulsion of the joint capsule attachment, but recent studies have shown that the ALL is usually attached to the Segond fracture fragment, and that the iliotibial band may also be involved.…”
Section: Mechanism Of Injury/pathologic Imaging Appearancesmentioning
confidence: 99%